Efektivitas Penerapan Job sheet Pembelajaran pada Mata Pelajaran Instalasi Motor Listrik di Sekolah Menengah Kejuruan - Rani Yuliani; Hendri Hendri (Jurnal Pendidikan Teknik Elektro, 2023)
This study aims to produce job sheet learning media that have been tested for feasibility through validity, practicality and effectiveness tests as a support in implementing practicum in the subject of Smart Relay-based Electric Motor Installation. This research was conducted on class XII students of SMK Negeri 5 Padang. This research phase uses the Research & Development (R&D) method, with a 4-D (Four-D) development model. The research data were obtained from instrument sheets or questionnaires to test validity and practicality, as well as performance sheets in the form of rubrics to test effectiveness. The data analysis technique in this study is descriptive quantitative. The results of the validity test of the Smart Relay-based Electric Motor Installation Practicum Job sheet are declared in the valid category. The results of the job sheet practicality test based on the responses from the Electric Motor Installation subject teacher were stated in the very practical category, and the practicality test results based on student responses were stated in the very practical category. The results of the job sheet effectiveness test stated that the job sheet was effective based on student learning outcomes in the very good category.